PharmMapper Server and Molecular Docking Study Focusing on Polydatin to Identify Potential Targets - Ferrari, Ivan Vito; Gregorio, Alex De; Fuggetta, Maria Pia; Ravagnan, Giampietro (European Journal of Applied Sciences, 2023)
In this short communication, we focused on the biological role of polydatin through two computerized analyzes (phamacophore study by PharmMapper server and molecular docking by Autodock vina with the Pyrx program). According to the best normalized fit scores calculated by the PharmMapper database, polydatin may be attractive for the following potential targets: Triggering receptor expressed on myeloid cells 1,Ephrin type-B receptor 4;Tyrosine protein kinase (HCK); ADP -ribose pyrophosphatase, mitochondrial,Putative ATP-dependent Clp protease proteolytic subunit; mitochondrial; Seprase and Caspase-3, ranked by normalized fit score in descending order (0.9921 to 09812). All these potential targets calculated by PharmMapper server are used after by docking method by utodock Vina with Polydatin. From the results of the binding energies of our docking approach only 3 potential targets play a key role for polydatin: the trigger receptor expressed on myelod cells, mithocondrial ADP -ribose pyrophospatase, and seprase (fibroblast activation protein). However, further computational analysis and in vitro and in vivo assays are required to confirm our preliminary results.